Living media interfaces: a multi-perspective analysis of biological materials for interaction. Issue 1 (2nd January 2020) - Merritt, Timothy; Hamidi, Foad; Alistar, Mirela; DeMenezes, Marta
ABSTRACT: Living media interfaces (LMIs) have emerged as a new way to interact with digital systems by incorporating actual living organisms in user interfaces. There is increasing interest in utilizing living media in the context of interaction design influenced by recent advancements in biological sciences that make new forms of responsive living media possible. We establish a definition of LMIs appropriate for HCI's interdisciplinary domain. We provide an overview of the current design space and identify open research questions from four different perspectives: Biological, Ethical, Artistic, and HCI. For each perspective, we use a series of LMI exemplars to illustrate and ground themes and arguments. We conclude with a series of implications for design, including a discussion of LMIs' ability to engage human users through being alive, their potential to symbolize and embody dynamic information, and the practical and ethical questions that designers need to consider when working with them.